Parasite found in parakeets - Study on 167 birds - Vili-Robert Voichitoiu; Viorel Herman; Narcisa Mederle (Medicamentul Veterinar, 2014)
The budgerigar (Melopsittacus undulatus) is a small, long-tailed, seed-eating parrot. Parakeets are the only species in the Australian genus Melopsittacus, and are found wild throughout the drier parts of Australia where this species has survived harsh inland conditions for the last five million years. The researches were conducted in two counties, Timis and Mehedinti throughout nine months, including 167 birds which were parasitologicaly controlled. The results that were analyzed to Faculty of Veterinary Medicine from Timisoara revealed: 18,56 % (31 birds) for Eimeria spp., next were the feathers lice, 16,16% (27 birds), scaly leg mites 8,38% (14 birds) and at the fine ascaridiasis (1%).